Pengaruh Pelayanan Dan Keunggulan Produk Terhadap Kepuasan Nasabah Pada Bank Muamalat Balaikota Medan - Fitri, Fitri (Jurnal Manajemen Akuntansi (JUMSI), 2023)
The background of the research in this thesis is that besides implementing the best service, bank Muamalat Balaikota Medan always strives to provide quality and superior products compared to products owned by other banks as competitors. Product excellence was created by Bank Muamalat, the Medan City Hall. Quality of service and quality of product excellence for customers can affect customer satisfaction. In the long term, customer satisfaction can be the main goal for marketing strategy planners in banking. The data used in this research is primary data obtained from the results of a questionnaire that has been filled out by the customers of the Mumala City Hall Medan Bank who are the research samples. In this research I used the data normality test with multiple regression tests and hypothesis testing. From the results of multiple regression analysis, it can be concluded that service variables affect customer satisfaction at Muamalat Medan City Hall with a significance level of 0.001, then product excellence variables affect customer satisfaction at Medan City Hall with a significance level of 0.11. Meanwhile, from the F test, it turns out that the service factor is a factor that has more influence on customer satisfaction at Bank Muamalat Balai Kota Medan than product excellence.